Conceptualisation and development of the arm activity measure (ArmA) for assessment of activity in the hemiparetic arm. (7th January 2013) - Ashford, Stephen; Slade, Mike; Turner-Stokes, Lynne
Abstract: Purpose: To develop a patient reported outcome measure of active and passive function in the hemiparetic upper limb. Methods: Potential items for inclusion were identified through (a) systematic review and analysis of existing measures and (b) analysis of the primary goals for treatment in a spasticity service. Item reduction was achieved through consultation with a small, purposively selected multi-disciplinary group of experienced rehabilitation professionals ( n  = 10) in a three-round Delphi process. This was followed by a confirmatory survey with a larger group of clinicians ( n  = 36) and patients and carers ( n  = 13 pairs). Results: From an initial shortlist of 75 items, 23 items were initially identified for inclusion in the arm activity measure (ArmA), and subsequently refined to a 20-item instrument comprising 7 passive and 13 active function. In common with the six measures identified in the systematic review, a five-point ordinal scaling structure was chosen, with ratings based on activity over the preceding 7 days. Conclusions: The ArmA is designed to measure passive and active function following focal interventions for the hemiparetic upper limb. Content and face validity have initially been addressed within the development process. The next phase of development has involved formal evaluation of psychometric properties. Implications for Rehabilitation: In clinical practice or research, outcome measures in rehabilitation need to have face and content validity. Following stroke or brain injury, goals for rehabilitation of the hemiparetic upper limb may be: to restore active function, if there is return of motor control or to improve passive function making it easier to care for the limb (e.g. maintain hygiene) if no motor return is possible, measurement of both constructs should be considered. This study describes the systematic development of the ArmA, a measure of active and passive function in the hemiparetic upper limb.